State Responsibility to Provide a Free Legal Aid Access for the Poor and the Obstacles in the Implementation - Derry Angling Kesuma (The Indonesian Journal of International Clinical Legal Education, 2019)
Access to legal aid for economically disadvantaged groups covers criminal, civil, and state administrative matters through both litigation and non-litigation mechanisms. However, the implementation of free legal assistance in Indonesia continues to face structural, administrative, and procedural barriers. This study identifies key obstacles, including the failure of investigators to guarantee suspects’ rights to free legal counsel as mandated by Article 56 of the Criminal Procedure Code, largely due to the absence of explicit juridical sanctions for non-compliance. Additional constraints include limited budget allocation, administrative difficulties in verifying indigency status, defendants’ reluctance to be represented by appointed counsel, the unavailability of legal aid posts (POSBAKUM) in several courts, low remuneration for legal advisors, and inconsistent attendance of appointed legal counsel during trial proceedings. Furthermore, defendants who cannot obtain certificates of indigency—particularly those detained or residing outside the court’s jurisdiction—face significant challenges in accessing legal aid, resulting in delays in fund disbursement. These findings underscore the need for policy reforms to strengthen institutional support, improve enforcement mechanisms, and ensure equal access to justice for the poor.